Prevalence of antibiotic resistance in Salmonella Typhimurium isolates originating from Iran: a systematic review and meta-analysis - Narimisa, Negar; Razavi, Shabnam; Masjedian Jazi, Faramarz (Frontiers in Veterinary Science, 2024)
Objective: Antibiotic resistance in Salmonella represents a significant global public health concern. Among various serovars, Salmonella enterica serovar Typhimurium is prevalent in multiple countries. This study aims to conduct a systematic review and meta-analysis to evaluate the pattern of antibiotic resistance in S. Typhimurium isolates from diverse sources in Iran.We conducted a comprehensive and systematic search for relevant articles until December 2023 in the following databases: PubMed, Scopus, Web of Science, and SID. The collected data were analyzed using Stata software version 17.Results: Eighteen studies examined the pattern of antibiotic resistance in S. Typhimurium for various antibiotics in Iran. Piperacillin and tetracycline exhibited the highest resistance rates, at 79% and 60% respectively, while cefixime and ceftriaxone had the lowest resistance rates at 0%.Our findings indicate a high level of antibiotic resistance among the studied antibiotics. This high level of antibiotic resistance raises concerns and underscores the necessity for monitoring the use of antibiotics. Moreover, resistance to these antibiotics was more prevalent in samples isolated from animals compared to other sources. This highlights the importance of animal screening to detect the presence of drug-resistant isolates, with the ultimate goal of reducing antibiotic resistance and preventing the transmission of resistant strains to humans.